Plant growth, fruit production, and total terpenoid production in bitter melon (Momordica charantia L.) with guano fertilizer application - Anna Moslihat Jamil; Maya Melati; Sandra Arifin Aziz (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Bitter melon (Momordica charantia L.) is valued for its anti-diabetic properties due to terpenoid compounds like charantin, but production struggles to meet market demands. This study aimed to analyze the response of plant growth characteristics, fruit production, and terpenoid compound production in bitter melon fruit by improving phosphorus availability through guano fertilizer application as additional organic fertilizer in organic cultivation. The experiment was conducted from May to September 2024 at the IPB experimental station in Cikarawang, Bogor, Indonesia. The experiment used a randomized complete block design with varying guano fertilizer doses (0, 152, 304, and 456 g per plant). Observations were conducted on 10 sample plants per experimental unit. The observed characteristics included vegetative and reproductive growth, fruit production, and total terpenoid production. Terpenoid analysis was performed using a colorimetric method with an ELISA reader. The results showed that guano fertilizer significantly affected several plant growth and production variables. Higher doses increased several values of vegetative growth parameters, flower numbers, and fruit production. The 304 g guano per plant yielded the highest concentration and production of terpenoids. This study demonstrates the potential of guano fertilizer to enhance bitter melon growth, yield, and terpenoid content, contributing to improved production to meet market demands. Keywords: net assimilation rate; organic; phosphorus; relative growth rate